Who is at risk for measles in Italy? Continued measles outbreaks in 2019 and barriers to elimination. (30th September 2020) - Filia, A; Bella, A; Del Manso, M; Baggieri, M; Magurano, F; Iannazzo, S; Sabbatucci, M; Nicoletti, L; Rota, M C
Abstract: Background: Measles is a highly contagious vaccine preventable disease that can lead to serious complications, including death. All five regions of the World Health Organization have set targets to eliminate measles. In Italy, measles vaccination was introduced in 1976, with sustained low uptake in the 1980s and 1990s. Uptake improved in subsequent years but never reached 95% coverage required for elimination. Two doses of measles-mumps-rubella (MMR) vaccine are recommended (at 12-15 months and 5-6 years respectively). Since July 2017, MMR vaccine has become mandatory for all children up to 16 years of age. Large outbreaks continue to occur, with over 8.000 cases reported in 2017-2018. Methods: We analysed measles cases reported to the national integrated measles and rubella surveillance system during January 1 - December 31, 2019. Results: From 1 January to 31 December 2019, 1, 627 cases (87% laboratory-confirmed), were reported from all 21 administrative regions. National incidence was 27 cases/million. Overall, 86% of cases were unvaccinated. Median age was 30 years but the highest incidence was in infants below one year of age. Ninety-six cases were reported amongst healthcare workers and transmission in the healthcare setting was frequent. Overall, 31% of cases reported complications, including three cases of encephalitis (in two adults and one child) and one death in an adult patient. Complications were more frequent in cases ≥20 years of age compared to younger patients. Forty-six percent of cases were hospitalised. Conclusions: The median age of cases has increased further in 2019 compared to 2017 (27 years) and 2018 (28 years). The proportions of complicated and hospitalised cases are high, this may be due to the high median age of cases but also to underreporting from general practitioners who are likely to see milder cases. Wide immunity gaps among adults (including healthcare workers) and nosocomial transmission are major challenges to measles elimination in Italy. Key messages: Measles is still endemic in Italy and large outbreaks continue to occur, with a significant public health impact. Wide immunity gaps among adults (including healthcare workers) and nosocomial transmission are major challenges to measles elimination in Italy.